KENYAMANAN TEMPAT KERJA PUSTAKAWAN: PERSPEKTIF ERGONOMI - fadmawati, endang (STAIN Ponorogo, 2014)
Factors considered onÂ the work areÂ the work environment, hardware, and cooperation between the computerâs users. AnÂ increase onÂ productivityÂ isÂ aÂ librarianÂ purpose.Â However,Â workÂ inÂ theÂ office (library)Â canÂ alsoÂ haveÂ anÂ impactÂ thatÂ is notÂ goodÂ forÂ theÂ safetyÂ and health librarians. So it is necessary to know how safe and well in the use of work equipment in the library in order to avoid accidents and other health problems. In short, ergonomicsÂ is the study of human behavior related to his job.